Bond strength of Epiphany (TM) Sealer combined with different adhesive systems photo-activated with LED and QTH - Minto, A. M. P.; Bandeca, Matheus Coelho [UNESP]; Borges, A. H.; Nadalin, M. R.; Thome, L. H. C. (Maik Nauka/interperiodica/springer, 2009)
The Epiphany (TM) Sealer is a new dual-curing resin-based sealer and has been introduced as an alternative to gutta-percha and traditional root canal sealers. The canal filling is claimed to create a seal with the dentinal tubules within the root canal system producing a 'monoblock' effect between the sealer and dentinal tubules. Therefore, considering the possibility to incorporate the others adhesive systems, it is important to study the bond strength of the resulting cement. Forty-eight root mandibular canines were sectioned 8-mm below CEJ. The dentine discs were prepared using a tapered diamond bur and irrigated with 1% NaOCl and 17% EDTA. Previous the application Epiphany (TM) Sealer, the Epiphany (TM) Primer, AdheSE, and One Up Bond F were applied to the root canal walls. The LED and QTH (Quartz Tungsten Halogen) were used to photo-activation during 45 s with power density of 400 and 720 mW/cm(2), respectively. The specimens were performed on a universal testing machine at a cross-head speed of 1 mm/min until bond failure occurred. The force was recorded and the debonding values were used to calculate Push-out bond strength. The analysis of variance (ANOVA) and Tukey's post-hoc tests showed significant statistical differences (P < 0.05) to Epiphany (TM) Sealer/Epiphany (TM) Primer/QTH and EpiphanyTM Sealer/AdheSE/QTH, which had the highest mean values of bond strength. The efficiency of resin-based filling materials are dependent the type of light curing unit used including the power density, the polymerization characteristics of these resin-based filling materials, depending on the primer/adhesive used.